Elastic TiO2-embedded silicone oil-(poly)dimethylsiloxane membrane for compliant robotics - Ahmad Farimin, Ahmad Osman; Chan, Kah Yoong; Lee, Chu Liang; Shamsul, Zakaria (IEEE, 2024)
Polydimethylsiloxane (PDMS) is essential in compliant robotics due to its versatility, elasticity, and biocompatible properties. Despite all the advantages, PDMS has a drawback of low dielectric permittivity, requiring high electric fields for significant actuation strains, which is the main cause leading to premature membrane breakdown. This paper investigates a dual-filler embedding approach using titanium dioxide (TiO2) and silicone oil (SO) to enhance the electromechanical properties and elasticity of PDMS membranes. A PDMS pre-blend was prepared by mixing commercial PDMS with a specified ratio of TiO2 and SO, forming single-filler and dual-filler systems, followed by curing in a laboratory oven. The membranes were subsequently characterized through uniaxial tensile testing to determine tensile strength, elongation at break, and Young's modulus. Breakdown strength analysis was conducted using a breakdown tester with step-up voltage, while relative permittivity was examined with an impedance analyzer within a frequency range of 30 MHz to 20 Hz. The dual-filler approach significantly improved tensile properties and elasticity, making PDMS membranes suitable for compliant robotics. This hybrid strategy creates a TiO2-embedded silicone oil-(poly)dimethylsiloxane composite membrane capable of withstanding extensive deformation thereby improving the performance and elasticity of compliant robotic systems.